From real to virtual: adaptation model of performance arts during covid-19 period - Harry Nuriman; Setiawan Sabana; Intan Rizky Mutiaz; Rikrik A. Kusmara (Jurnal Sosioteknologi, 2020)
Large-scale Social Restrictions (PSBB) due to the Covid-19 outbreak affected all aspects of life including the performing arts. The prohibition of the crowd which is characteristic of a conventional show forces the creators and performers to adapt. One of the ways taken is to adapt the show in the real world (real) to the virtual world (virtual) and sacrifice a number of aspects of the performing arts. This research develops a performance model of the Dipanegara Storybook which is transformed from the real world performance to the virtual world. This qualitative descriptive study uses an experimental method. Modeling is performed on the performance space, the viewer, as well as interactivity and audience involvement using digital technology, including 3D modeling, motion capture, augmented reality and real time game engine. Based on the developed model, this research has succeeded in identifying a number of aspects that can be adapted, as well as the advantages and disadvantages arising from these adaptations.Seni